Virasoro Hair and Entropy for Axisymmetric Killing Horizons - Chen, Lin-Qing (2020)
We show that the gravitational phase space for the near-horizon region of a bifurcate, axisymmetric Killing horizon in any dimension admits a 2D conformal symmetry algebra with central charges proportional to the area. This extends the construction of Haco et. al. [J. High Energy Phys. 12 (2018) 098] to generic Killing horizons appearing in solutions of Einstein's equations and motivates a holographic description in terms of a 2D conformal field theory. The Cardy entropy in such a field theory agrees with the Bekenstein-Hawking entropy of the horizon, suggesting a microscopic interpretation. A set of appendixes is included in the Supplemental Material that provides examples and further details of the calculations presented in the main text.